Gender specificities of attitude towards disease in children and adolescents with chronic somatic disorders - Kukuruza, Hanna V.; Kyrylova, Olena O. (Psychological Counseling and Psychotherapy, 2019)
The article defines the specificities of attitude towards disease in children and adolescents, both male and female, with rheumatoid arthritis that is a chronic disorder. We have analysed the awareness of adolescents as for their disease, their openness towards perception of new information as well as their motivation for fighting the disease. We have studied psychological reactions of the adolescents in terms of the disease and defined types of attitudes towards it. We have found that girls are characterized by the highest level of anxiety due to their disease, although they are active in their fight with it, and the harmonious type of attitude was reliably registered more frequently. Boys expressed the highest level of guilt. They were characterized by a deliberate position as for their trust towards doctors. In their cases, ergopathic and sensitive types of attitude were most expressed.